2010
DOI: 10.1002/ange.201000593
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Atomistic Description of DNA Unfolding

Abstract: Despite recent efforts, the folding/unfolding of DNA (understood as a dramatic conformational change from the native conformation in a significantly large portion of the duplex) is still poorly described. A range of classical physical studies led to the assumption that the unfolding of short DNA fragments is reversible and follows a two-state mechanism, starting at d(A·T) pairs. [1][2][3] Nevertheless, this traditional view has been recently challenged [4][5][6][7][8][9] by ultrafast techniques, which suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…24 Experiments and theory have shown that this oligonucleotide folds on a (multi)microsecond time scale 2527 in water, and should unfold on a similar time scale in a denaturant solvent such as pyridine. 22 The small size of the system accelerates calculations, favors sampling, and reduces memory effects, which might be very important for longer oligonucleotides. Previous studies have demonstrated the ability of current force field and MD protocols to simulate this structure properly in a variety of environments.…”
Section: Methodsmentioning
confidence: 99%
“…24 Experiments and theory have shown that this oligonucleotide folds on a (multi)microsecond time scale 2527 in water, and should unfold on a similar time scale in a denaturant solvent such as pyridine. 22 The small size of the system accelerates calculations, favors sampling, and reduces memory effects, which might be very important for longer oligonucleotides. Previous studies have demonstrated the ability of current force field and MD protocols to simulate this structure properly in a variety of environments.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the long timescales involved in the structure formation process of nucleic acids the reverse process of unfolding stable structures has been studied using MD simulations at elevated temperatures . The increased simulation temperature can significantly accelerate conformational transitions and shifts relative free energies of conformational states and can lower free energy barriers.…”
Section: Computational Approaches For Structure Prediction Of Rnamentioning
confidence: 99%
“…Similar to unfolding of proteins, the study of the unfolding process of nucleic acids can also give insights into putative intermediate states of the folding process. The method has been used extensively to study the coupled dissociation and unfolding of a DNA duplex dodecamer and the unfolding of nucleic acid hairpin structures . Alternatively, unfolding can be induced by applying an external force on the molecule to disrupt a key interaction that stabilizes the 3D conformation.…”
Section: Computational Approaches For Structure Prediction Of Rnamentioning
confidence: 99%
“…In the view of the complexity of problems related to the DNA physics, computer modeling has always played an important role in bridging the gap between the bulk experiments and molecular‐level understanding. The currently available all atom (AA) force fields have significantly evolved since their inception in the 1980s21,22 and are now able to reproduce a diverse set of subtle structural fluctuations that take place from pico‐ to microsecond timescales 23–27…”
Section: Introductionmentioning
confidence: 99%